2020
DOI: 10.1017/s0033291720004171
|View full text |Cite
|
Sign up to set email alerts
|

An ecological study of objective rest–activity markers of lithium response in bipolar-I-disorder

Abstract: Background Despite its pivotal role in prophylaxis for bipolar-I-disorders (BD-I), variability in lithium (Li) response is poorly understood and only a third of patients show a good outcome. Converging research strands indicate that rest–activity rhythms can help characterize BD-I and might differentiate good responders (GR) and non-responders (NR). Methods Seventy outpatients with BD-I receiving Li prophylaxis were categorized as GR or NR according to the ratings on the retrospective as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…[14][15][16][17] Furthermore, circadian markers associated with fragmentation, variability, amount and/or amplitude of day-and night-time activity may discriminate good from poor lithium responders. 18 The above findings support the potential value of assessing and monitoring CRAR in BD. However, laboratory assessments and mobile devices collating objective data are primarily employed in research rather than day-to-day clinical settings.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…[14][15][16][17] Furthermore, circadian markers associated with fragmentation, variability, amount and/or amplitude of day-and night-time activity may discriminate good from poor lithium responders. 18 The above findings support the potential value of assessing and monitoring CRAR in BD. However, laboratory assessments and mobile devices collating objective data are primarily employed in research rather than day-to-day clinical settings.…”
supporting
confidence: 58%
“…More recently, research has explored circadian patterns of motor activity as estimated by phase, amplitude, intradaily stability and/or interdaily variability of activity and these actigraphy markers of CRAR were suggested to discriminate BD cases from controls 14‐17 . Furthermore, circadian markers associated with fragmentation, variability, amount and/or amplitude of day‐ and night‐time activity may discriminate good from poor lithium responders 18 …”
Section: Introductionmentioning
confidence: 99%
“…When investigating the response to lithium, a long-standing mood-stabilizing pharmacological treatment for BD, individuals who responded well as assessed by the Retrospective Assessment of Response to Lithium Scale (the Alda scale) were also found to have more regular rest-activity patterns following treatment, as measured by IV and RA ( 107 ). Further, when using principal components analysis to classify lithium responders based on their actigraphy parameters, the same investigative group ( 108 ) found that circadian rhythmicity markers involving regularity and stability in patterns (RA, IV, IS, as well as M 10 activity) were able to correctly classify 64% of BD cases as good responders as determined by the Alda scale.…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions in rest-activity patterns are shown to persist during euthymia [e.g., ( 14 , 16 , 89 )] and there is preliminary evidence that distinct patterns may differentiate BD from other major mood and psychotic disorders, and within subtypes of BD ( 7 , 69 , 81 ). Both pharmacological and non-pharmacological therapies have demonstrated rest-activity pattern stabilization associated with improvements in mood symptoms [e.g., ( 107 , 113 )]. However, the mechanisms by which these occur are yet to be fully uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Luckily enough, though, the mind-brain problem does not need to be solved to advance in precision psychiatry. Pharmacogenetics (Vilches, Tuson, Vieta, Álvarez, & Espadaler, 2019), behavioral biomarkers (Scott, Hennion, Meyrel, Bellivier, & Etain, 2020) or mHealth (Hidalgo-Mazzei et al, 2018), for instance, are areas of precision psychiatry that do not rely on deciphering the biology of mental disorders and still can lead to more precise and personalized treatments.…”
mentioning
confidence: 99%